Penerapan Model Pembelajaran Cooperative Learning Tipe Snowball Trowing untuk Meningkatkan Hasil Belajar IPS Konsep Masalah Sosial Pada Kelas IV SD Negeri 3 Kota Ternate - Sufri Saleh (Peneliti.net, 2020)
This study used the Class Action Research (CAR) method with the subject of Class 1V SD Negeri 3 Ternate City with a total of 25 students consisting of 12 boys and 13 girls, this research was carried out in 2 cycles. The results of this PTK are as follows: in cycle 1 and the teacher is not familiar with the social studies learning atmosphere by using the cooperative learning model of snowball trowing type, student activity is still low, individual evaluation scores, students only get a slight increase, namely 6.6% from the desired KKM, which is 60 scores only get an average The average score is 66.6 of the total 25 students or 20% who still have not reached the KKM or are said to have not completed, and 12 students or 48% who are not involved in group discussion group discussions. In cycle ii students are getting used to the learning model given in social studies learning, especially the teacher who displays media images of social problems. Student activity got an increase as evidenced by all students involved in group discussions, student evaluation scores also increased by an average score of 74.8 or 74.8%. all achieved the KKM target and 4 students or 16% of students scored very well. Based on the study of research results, it can be concluded that social studies learning in Class 1V SD Negeri 3 Ternate City by using the cooperative learning model of snowball trowing type can improve student learning outcomes. Thus, the authors suggest that in the social studies learning process on the concept of social problems, use a cooperative learning model of the snowball trowing type in order to achieve the desired learning objectives.